ECONOMIC INDEPENDENCE IN POOR URBAN COMMUNITIES IN MENDAWAI SOCIAL COMPLEX, PALANGKA RAYA CITY - Netanyahu, Kurniawan; Wirawan, Aprianto; Jeniva, Isabella; Widyasari, Yolantya; Inriani, Eva; Malau, Reynhard; Juniari, Rindi; Tirayoh, Marlon (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Urban communities living in the Mendawai Social Complex, Palangka Raya City are facing various economic challenges, especially income instability due to odd jobs such as construction workers and traditional miners. Community Service (PKM) activities use the Participatory Action Research (PAR) method. Considering the large area of the PKM location, researchers invite active participation from the GKE Panenga Congregation, which also experiences the same economic problems, to find solutions to these problems. The purpose of this PKM activity is to improve community welfare through three main aspects, namely independence, social capital, and life skills. The results of this PKM activity show that participants can find references for independent businesses that have the potential to increase income through life skills training in the culinary field. Participants also obtain solutions in managing business groups so that they can be sustainable through business coordination training provided by practitioners. Then, there is a re-strengthening of the social capital of the participants through solutions to social problems provided during the PKM activity. In addition, another quite prominent result of this PKM activity is that it not only has a positive impact on the participants but also on the Mendawai Social Complex community, namely the existence of a reference for a business model that can be developed independently. At the end of this PKM activity which uses the Community Based Development (CBD) approach and produces effective community empowerment activities, the researcher suggests that both the government and other private parties also use the same approach to the Mendawai Social Complex community, or other urban communities who are trapped in poverty.